2017
DOI: 10.1158/1078-0432.ccr-16-1874
|View full text |Cite
|
Sign up to set email alerts
|

FCGR Polymorphisms Influence Response to IL2 in Metastatic Renal Cell Carcinoma

Abstract: Background Fc-gamma receptors (FCGRs) are expressed on immune cells, bind to antibodies, and trigger antibody-induced cell-mediated anti-tumor responses when tumor-reactive antibodies are present. The affinity of the FCGR/antibody interaction is variable and dependent upon FCGR polymorphisms. Prior studies of cancer patients treated with immunotherapy indicate that FCGR polymorphisms can influence antitumor response for certain immunotherapies that act via therapeutically administered mAbs or via endogenous tu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…FCGR polymorphisms can alter the affinity of FCGRs for the Fc portion of antibodies (mAbs or endogenous antibodies) ( 37 ). For example, in a separate study of patients with metastatic renal cell carcinoma treated with high-dose IL-2, we found that patients with a “higher affinity” FCGR genotype had improved clinical outcome as compared to those patients with a “lower affinity” FCGR genotype ( 38 ). In our analysis of those same metastatic renal cell carcinoma patients for KIR/KIR-ligand genotype influence on outcome, we did not observe differences in clinical outcome associated with KIR3DL1 and HLA-Bw4 genotype status ( 39 ).…”
Section: Discussionmentioning
confidence: 90%
“…FCGR polymorphisms can alter the affinity of FCGRs for the Fc portion of antibodies (mAbs or endogenous antibodies) ( 37 ). For example, in a separate study of patients with metastatic renal cell carcinoma treated with high-dose IL-2, we found that patients with a “higher affinity” FCGR genotype had improved clinical outcome as compared to those patients with a “lower affinity” FCGR genotype ( 38 ). In our analysis of those same metastatic renal cell carcinoma patients for KIR/KIR-ligand genotype influence on outcome, we did not observe differences in clinical outcome associated with KIR3DL1 and HLA-Bw4 genotype status ( 39 ).…”
Section: Discussionmentioning
confidence: 90%
“…It had two polymorphic alleles at the amino acid position, which was associated with an increased risk of GC patients [20]. Clinical studies have reported that FCGR2A polymorphisms are associated with the clinical outcome of tumours, including colorectal cancer, neuroblastoma and renal cell carcinoma [21][22][23][24]. In contrast, either FCGR2A or FCGR3A polymorphisms affect the clinical outcome of follicular lymphoma patients [25].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, high doses of IL-2 were approved by the FDA in 1992 to treat patients with metastatic RCC [78,193]. Evaluating data from a cohort of patients treated with high doses of IL-2, it was found that when the higher-affinity genotypes for FCGR2A, FCGR3A, and FCGR2C were considered together, they were associated with increased tumor shrinkage and prolonged survival [194]. FCGR3A encodes for CD16 expressed on NK cells.…”
Section: Nk Cells and Renal Cell Carcinomamentioning
confidence: 99%